Restricting Intake and Increasing Energy Improves Efficiency in Newly Received Growing Cattle and Zelnate Has No Effect - T. Spore; S. P. Montgomery; E. Titgemeyer; G. A. Hanzlicek; Christopher Vahl; T. G. Nagaraja; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objectives:Study effects of two limit-fed diets formulated to provide two levels of dietary energy and offered at two different intake rates to target similar gains and analyze the efficacy of a novel DNA-immunostimulant administered on arrival. Study Description:A 56-day pen study was conducted utilizing 370 Angus × Brahman heifers shipped from Florida (1,455 mi) to study the effects of limit-feeding at 2 intakes based on prior research conducted at the Kansas State University Beef Stocker Unit, Manhattan, KS, to achieve similar gains and effects of Zelnate under the dietary conditions. The Bottom Line:Limit-feeding a higher-energy, lower-roughage diet at 2.2% of body weight daily is a more efficient feeding strategy than offering a higher-roughage, lower-energy diet at 2.4% of body weight daily to achieve similar gains, and Zelnate administered on arrival had no effect on performance or health.
Keywords: stocker cattle; limit-feeding; zelnate